Relationship between Leg Muscle Power and Shooting Ability in Soccer Games - Jud; Rusli, Muhammad; Marsuna (S&Co Publishing, 2025)
The purpose of this study was to determine the relationship between leg muscle power and soccer shooting ability. The researcher wanted to determine the relationship between leg muscle power and shooting ability in soccer games in students of SMA Negeri 10 Kendari using a descriptive method with a correlational design. The population of this study was fifty students of class XI of SMA Negeri 10 Kendari. Sampling was carried out by purposive sampling, especially using the criteria of male gender, as the basis for determining the sample. Thus, the research sample consisted of 21 students. To measure leg muscle power, a standing long jump test was used and to measure shooting ability, a shooting test was used. Based on the statistical analysis of the correlation test with the SPSS 25 application, the variables of shooting ability and leg muscle power have a positive relationship. The calculated r value is 0.505 with a significance level of 0.038 <0.05 and a coefficient of determination of 0.327 or 32.7%. This shows that shooting ability in soccer matches is significantly correlated with leg muscle power. Both variables have a moderate relationship when shown on the correlation map. Leg muscle strength contributed 32.7% of shooting ability, while other physical condition parameters including strength and endurance contributed the remaining 67.3%. Speed, accuracy, coordination, and flexibility. According to the research findings, shooting ability in a soccer match was significantly correlated with leg muscle strength.